A new fossil species of the genus Coptodera Dejean, 1825 (Coleoptera: Carabidae: Lebiinae) from Baltic amber - Gamboa, Sara; Ortuño, Vicente M. (Zootaxa, 2015)
In this paper a new species of fossil ground-beetle, Coptodera elektra n. sp. (Coleoptera: Carabidae) preserved in a piece of Baltic amber (Eocene) is described and the paleobiology of the species is studied. This new species represents the first known fossil record for the genus, as well as the first record of its presence in Europe.